The Effects of a Three-Arm Hammer Cracker/ Beater on the Performance of a Newly Developed Palm Kernel Shell Cracking Machine - Alexander A. Offiong; Aniekan Offiong; A.P. Ihom; I.E. Markson (Archives of Current Research International, 2024)
The effects of a 3-arm hammer cracker/ beater on the performance of a newly developed palm kernel shell cracking machine have been determined. The newly developed palm kernel cracker was equipped with a 3-arm hammer beater shaft, and a constant weight of 3000g of palm kernel shells were cracked under various operating speeds ranging from 800- 1600 rpm. During this period the performance of the newly developed machine equipped with the 3-arm hammer beater was evaluated. It was discovered that the 3000g of palm kernel nuts were cracked in just 30.14 seconds at a speed of 1600 rpm. The number of whole nuts was 541 at the operating speed of 1000 rpm which was the highest of all the processing speeds used. It was also discovered that the number of uncracked nuts decreased with increasing operating speed. Unbroken nuts were 87 at 1000 rpm and were the lowest operational speeds used. For the number of cracked nuts it was discovered that the number of cracked nuts increased with an increase in cracking speed or operational speed. The work observed that the effective capacity of the machine equipped with the 3-arm hammer beater increased with an increase in operational speed. The cracking efficiency also increased with increasing operational speed. Un-cracked nuts loss was seen to decrease as the operational speed increased. The highest performance efficiency of 84.53, the highest overall efficiency of 82.95, and the smallest value of split nut loss of 13.59 all occurred at the operational speed of 1000 rpm. It is therefore recommended that for this newly developed palm kernel shell cracking machine equipped with a 3-arm hammer beater the best operating speed should be 1000 rpm, to minimize losses and enjoy high performance efficiency.